2020
DOI: 10.3390/agronomy10111735
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Resistance to Glyphosate and 2,4-D in Carduus acanthoides L. from Argentina and Alternative Control Solutions

Abstract: Carduus acanthoides L. is an invasive species native to Europe and distributed in other parts of the world, including North and South America. In Cordoba, Argentina, control failures of this species have been reported in Roundup Ready (RR) soybean crops where glyphosate and 2,4-D have frequently been applied, although there are no confirmed reports worldwide of resistance to glyphosate and 2,4-D in this species. Dose–response tests showed multiple-resistance to both active principles. The resistant population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…In the current study, we also determined the resistance patterns of the R population to different herbicides and found that they exhibited low levels of cross-resistance to ALS inhibitors and multiple resistance to PSII inhibitors. Similarly, metabolic resistance was identified in diverse weed species, endowing them with uncertain patterns of multiple resistance, such as plumeless thistle ( Carduus acanthoides L.) [ 43 ], Italian ryegrass ( Lolium multiflorum L.) [ 44 ], and late watergrass Echinochloa phyllopogon (Stapf) Koss [ 45 ]. Although the R population, LJ-01, was also resistant to thifensulfuron-methyl, pyrazosulfuron-ethyl, bromoxynil octanoate, and atrazine, it remained susceptible to rimsulfuron, tembotrione, mesotrione, and topramezone.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we also determined the resistance patterns of the R population to different herbicides and found that they exhibited low levels of cross-resistance to ALS inhibitors and multiple resistance to PSII inhibitors. Similarly, metabolic resistance was identified in diverse weed species, endowing them with uncertain patterns of multiple resistance, such as plumeless thistle ( Carduus acanthoides L.) [ 43 ], Italian ryegrass ( Lolium multiflorum L.) [ 44 ], and late watergrass Echinochloa phyllopogon (Stapf) Koss [ 45 ]. Although the R population, LJ-01, was also resistant to thifensulfuron-methyl, pyrazosulfuron-ethyl, bromoxynil octanoate, and atrazine, it remained susceptible to rimsulfuron, tembotrione, mesotrione, and topramezone.…”
Section: Discussionmentioning
confidence: 99%
“…Syringes were incubated at 27°C in the dark for 4 hours. The ethylene (C 2 H 4 ) in 1 mL of the gas at the top of the syringe was analyzed by gas chromatography (Palma-Bautista et al 2020). The C 2 H 4 content was expressed as nL g -1 fresh weight h -1 .…”
Section: Accumulation Of Shikimic Acid and Ethylenementioning
confidence: 99%